Ethical Considerations In Collaborative Practice: Examining The Ethical Frameworks Guiding Public Health And Social Workers (Journal of Namibian Studies : History Politics Culture, 2022)
Collaborative practice between nurses and social workers is vital for delivering comprehensive healthcare that addresses the diverse needs of patients. This collaboration presents various ethical challenges as professionals navigate complex healthcare contexts and intersecting ethical frameworks. This paper explores the ethical principles guiding nursing and social work, highlighting their intersection and implications for collaborative practice. Challenges such as differing perspectives, power dynamics, and resource constraints are examined, alongside strategies for ethical decision-making. Through open dialogue, mutual respect, and shared decision-making, interdisciplinary teams can promote patient-centered care, social justice, and ethical integrity.